Answer:
i will try my best to find the answer of question if i can
Step-by-step explanation:
Answer:
When Amina is 18. Saad would be;
k. 14
Step-by-step explanation:
Let "x" represent Anita's current age and let "y" represent Saad's current age, we have;
Anita's age = 2 × Saad's age
Therefore;
x = 2 × y...(1)
In 4 years, we will get;
x + 4 = 1.5 × (y + 4)...(2)
Substituting the value of x in equation (1) into equation (2), we get;
2·y + 4 = 1.5·y + 1.5 × 4 = 1.5·y + 6
2·y + 4 = 1.5·y + 6
2·y - 1.5·y = 6 - 4 = 2
0.5·y = 2
y = 2/0.5 = 4
Saad's current age = y = 4 years
From equation (1), we have;
x = 2 × y = 2 × 4 = 8
Amina's current age = x = 8 years
When Amina is 18, we have;
18 = 10 + 8 = 10 + x
Therefore, Amina would be 18 in 10 years time from now, from which we have;
Saad would be 10 years + y = 10 years + 4 years = 14 years in 10 years from now
Therefore, when Amina would be 18 years in 10 years from now Saad would be 14 years.
Hello from MrBillDoesMath!
Answer:
-1/16
Discussion:
Rewrite
((1/4 + 1/x)/(4+x)) as
(1/4 + 1/x) * (1/(4+x)) = => put num. over common denom,
( (x+4)/4x) * (1/(4+x)) = => cancel (x+4) from num. and denom.
(1/4x)
So as x ->-4, (1/4x) approaches ( 1/ ( 4 * (-4) ) ) = -1/16
Thank you,
MrB
Answer:
8/15
Step-by-step explanation: